Associations between maternal occupational exposures and pregnancy outcomes among Chinese nurses: a nationwide study - Zhaoqiang Jiang; Junfei Chen; Lingfang Feng; Mingying Jin; Shuang Liu; Lina Wang; Jing Wang; Changyan Yu; Jianhong Zhou; Yan Ye; Liangying Mei; Wenlan Yu; et al. (BMC, 2023)
Abstract Background Several studies have provided evidence about adverse pregnancy outcomes of nurses involved in occupational exposure. However, the pregnancy outcomes among nurses in middle-income countries are not well demonstrated. The main aim of this study is to present the prevalence and influencing factors of pregnancy outcomes among female nurses in China. Methods We included 2243 non-nurse health care workers, and 4230 nurses in this national cross-sectional study in China. Information on occupational exposures and pregnancy outcomes was collected using a face-to-face investigation. Odds ratios (ORs) were estimated through logistic regression. Results The proportion of threatened abortion, spontaneous abortion, and stillbirth of female nurses was 2.6%, 7%, and 2.1%, respectively. We found an increased risk of threatened abortion among nurses with overtime work (OR = 1.719, 95% CI 1.158-2.550). The risk of threatened abortion and spontaneous abortion was elevated among nurses handling disinfectant (OR = 2.293 and 1.63, respectively). We found a nearly twofold increased risk of premature birth (OR = 2.169, 95% CI 1.36-3.459) among nurses handling anti-cancer drugs. Conclusions Our findings suggested that maternal occupational exposures might be associated with the risk of adverse pregnancy outcomes among female nurses in China. We recommend that policy-markers and hospital managers work together to reduce exposure to occupational hazards and improve pregnancy outcomes among female nurses.